Strategi Pemasaran Pendidikan Madrasah Tsanawiyah Bali Bina Insani di Daerah Minoritas-Muslim Tabanan Bali - Syaifuddin Syaifuddin; Muhammad Fahmi; Hanik Alfiyah; Ilun Mualifah; M. Havera (UIN Sunan Ampel Surabaya, 2019)
This article reflects the study of marketing of education at Madrasah Tsanawiyah Bali Bina Insani (BBI). Located in a Muslim minority area, this institution implements marketing strategy that has implications in people's acceptance towards the Islamic educational institution. This study explores the MTs BBI strategy in marketing its institution through smooth but structured promotion. The success of the BBI institution is marked by the attitude of community acceptance that supports the existence of BBI through collective actions. As a managerial action in managing religious differences within surrounding community, the BBI academic community is required to be open and accommodating towards differences. This basic culture together with professional and transparent management becomes the main value in the marketing of institutions through digital media.